Can international elite sport success trickle down to mass sport participation? Evidence from Danish team handball - Storm, R. K.; Gjersing Nielsen, C.; Jakobsen, T. G. (European Journal of Sport Science, 2018)
Many scholars do not find evidence of a trickle-down effect from elite sport success to mass sport participation. Contrary to what is assumed by the trickle-down effect "theorem", successful elite sportspeople do not seem to inspire amateurs to take up sport themselves. However, recent studies present evidence that elite sport can have an influence. In this article, we apply regression models on time series data from one of the most successful Danish sports, team handball. Our findings are mixed, but lean towards supporting scholars who argue that trickle-down effects are not necessarily an inherent part of international sporting success. Further studies should examine more sports to identify where trickle-down effects occur and why